Social, Political and Cultural Dimensions of Health - Dew, Kevin; Scott, Anne.; Kirkman, Allison; SpringerLink (Online service) (Cham : Springer International Publishing (Imprint), 2016)
This book comprehensively explores social, political and cultural dimensions of health in contemporary society. It addresses many issues and pertinent questions, including the following: Are we over diagnosed and over medicated? How can patients participate in their own care? Do pharmaceutical companies coerce us into medication regimes? What drives inequalities in health outcomes? What is the experience of health care for indigenous communities? Why do different countries have such different health care systems? How do we respond to life-changing conditions? Can we achieve a 'good death'? How do new genetics shape our identities? Is public health a force of liberation or disempowerment? The book incorporates the range of levels of influence on health, covering individual patient experiences, the health professions, multinational corporations, the state, global organisations as well as examining trends in social organisation, cultural expression and technological developments. The volume provides an accessible, yet in-depth, overview and discussion of the sociology of health. The chapters include an illustrative case study and further readings relating to the topic.
Chapter 1. Introduction -- Chapter 2. Health Consumers and the Medical Encounter -- Chapter 3. Inequalities in Health -- Chapter 4. The Health of Indigenous Communities and Migrant Groups -- Chapter 5. Institutions of Health Care -- Chapter 6. Health Work -- Chapter 7. Medicalisation and Contested Illnesses -- Chapter 8. Pharmaceuticals -- Chapter 9. Chronic Illness and Disability -- Chapter 10. Death and Dying -- Chapter 11. Sexuality and Sexual Behaviour -- Chapter 12. Mental Health and Social Control -- Chapter 13. Technology and Health -- Chapter 14. New Genetics and Risk -- Chapter 15. Promoting Public Health -- Chapter 16. Health and the Media -- 17. Conclusion. .
Keywords: Quality of life; Political science